A Case Report of a Novel Atypical Mycobacterial Infection: Mycobacterium Chimaera Hand Tenosynovitis. Issue 3 (22nd July 2022) - McLaughlin, C.M.; Schade, M.; Cochran, E.; Taylor, K.F.
Abstract : Case: A 76-year-old fisherman with a history of diabetes mellitus, coronary artery bypass grafting, and a previous ipsilateral elbow wound presented with a 1-year history of hand pain and swelling. Anti-inflammatories and antibiotics were administered without improvement. Magnetic resonance imaging and ultrasound demonstrated flexor tenosynovitis. Intraoperative cultures revealed Mycobacterium chimaera . The treatment course included 2 tenosynovectomies and a 1-year course of triple antimycobacterial therapy. Conclusion: Nontuberculous mycobacteria infections should be considered in cases of indolent tenosynovitis. M. chimaera should be considered in patients with a history of cardiopulmonary bypass given its association with cardiopulmonary heater-cooler units.